Supramolecular Thiophene-Based Materials: A Few Examples of the Interplay between Synthesis, Optoelectronic Properties and Applications - Di Maria, Francesca; Zangoli, Mattia; Barbarella, Giovanna (Organic Materials, 2021)
Supramolecular nanostructured thiophene based materials with optoelectronic functions are of wide current interest and are playing a crucial role in different fields of nanoscience and nanotechnology. This short review gives a concise report of some particularly interesting examples from our own work concerning thiophene-based supramolecular architectures at multiple length scales, their function and application in devices. We start with some general considerations on the great chemical diversity of thiophene derivatives and their supramolecular architectures. Then we focus on how the supramolecular organization of specific thiophene derivatives may generate nanostructures that enable new functions and applications in devices. For each example, we report the synthesis of the corresponding thiophene derivatives.1. Introduction2. Supramolecular Organization may Impart New Functions to the System3. Supramolecular and Optoelectronic Properties of Oligothiophene-S,S-dioxides4. Colloidal Nanoparticles formed by Self-Assembly of Thiophene-Based Polymers5. Conclusions and Outlook
Keywords: thiophene supramolecular assemblies; synthesis; non-covalent interactions; functional self-assembly; nanoparticles